Detection of c.G2194A mutation in \(AR\) gene of a vietnamese patient with androgen insensitivity syndrome: a case report - Nguyen, Thu Hien; Nguyen Thi Kim, Lien; Nguyen, Huy Hoang; Nguyen Thi Thanh, Ngan; Tran Thi, Huong Giang; Nhung Nguyen, Hong; Phuong Mai, Nguyen Thi; Hoang Nguyen, Huy (Academia Journal of Biology, 2022)
Androgen insensitivity syndrome (AIS) is a rare X-linked recessive androgen receptor (AR) disorder. However, the overlap in clinical manifestations between AIS and other disorders of sex development can cause clinical diagnostic difficulties. Applying the whole coding region sequencing method is an optimal method for the diagnosis of AIS. In this study, whole-exome sequencing was performed to screen mutations in the AR gene as well as genes related to disorders of sex development (DSD). Sanger sequencing was applied to validate the mutations in the patient. One missense mutation in the AR gene which was reported previously was identified in the patient. In this site, nucleotide G is changed to A at position 2194 on cDNA (c.G2194A), leading to a substitution of aspartic at position 732 aspartic to asparagine (p.Asp732Asn). However, this is the first published case in a Vietnamese with this mutation. Our study expands the mutation spectrum of the AR gene in Vietnamese patients and confirms the usefulness of whole-exome sequencing in the diagnosis of AIS. The results of the study are the basis for supporting doctors in prenatal diagnosis and giving reasonable advice to patients and families.